Dynamics of C-reactive protein in conditions of substance P block - O. M. Shevchenko; V. O. Sych (Kazimierz Wielki University, 2020)
With the aim to determine the features of the concentration of C-reactive protein in the blood in carrageenan secondary chronic inflammation on the background of blockade of substance P an experimental prospective controlled randomized study was performed on 132 WAG rats in series of 6 rats each in the natural course and using a pharmacological aprepitant praparation - inhibitor of NK-1R in the control and simulated inflammation series for 6 hours, as well as 1, 2, 3, 5, 7, 10, 14, 21, 28 days. the peculiarities of the concentration of C-reactive protein in the blood in carrageenan secondary chronic inflammation on the background of blockade of substance P have been developed.